Emergency powers in Asia : exploring the limits of legality / edited by Victor V. Ramraj, Arun K. Thiruvengadam. - Ramraj, Victor Vridar, 1968-; Thiruvengadam, Arun K. (Cambridge University Press, 2010)
What is the relevance of contemporary debates over emergency powers for countries situated in Asia? What role does, and should, the constitution play in constraining these powers? The essays in this collection address these issues, drawing on emergency situations in over 20 countries in Asia as a ready-made laboratory for exploring the relationship between emergency powers and constitutionalism. This volume therefore rests squarely at the intersection of two debates - a debate over the ability of law to constrain the invocation and use of emergency powers by the executive in times of crisis, and a debate over the nature and viability of constitutionalism in Asia. At this intersection are fundamental questions about constitutionalism and the nature of the modern state, questions that invite legal, political, sociological and historical analysis.